The driving factors of energy-related CO2 emission growth in Malaysia: The LMDI decomposition method based on energy allocation analysis. (November 2019) - Chong, Chin Hao; Tan, Wei Xin; Ting, Zhao Jia; Liu, Pei; Ma, Linwei; Li, Zheng; Ni, Weidou
Abstract: Malaysia is a typical Southeast Asian country that is a dynamic part of the global growth of energy-related CO2 (carbon dioxide) emissions, but little research exists on the driving factors of its energy-related CO2 emission growth. Most of the related publications have considered only the effect of the change of economic indicators using econometric methods, and seldom have they considered the technical driving factors from the perspective of energy systems. In this study, a methodology called the logarithmic mean Divisia index (LMDI) decomposition method based on energy allocation analysis was applied to define the contributions of technical driving factors related to the growth of CO2 emissions in Malaysia during the periods 1978–1990, 1990–2002, and 2002–2014. The technical driving factors include end-use energy structure, electricity generation efficiency, and fuel-mix in electricity generation. The results indicate that, although the population, GDP per capita and energy intensity are still the main driving factors influencing the changes of energy-related CO2 emissions in Malaysia, the influence of technical driving factors is increasing from in 1978–2014. The increasing ratio of electricity in the end-use stage and the structural changes of fuel-mix in electricity generation contribute to energy-related CO2 emission growth. Meanwhile, the increasing end-use energy efficiency and electricity supply efficiency effectively slow down CO2 emissions in Malaysia. Compared with previous publications, the technical driving factors considered in this study can provide a more detailed explanation for the interaction between energy, the economy, and CO2 emissions. On the basis of an overview of Malaysia's existing policies, policy recommendations for further control of energy-related CO2 emissions in Malaysia that mainly focus on these technical factors were proposed. Highlights: Driving factors analysis behind energy-related CO2 emission growth in Malaysia. Perspectives from economic development and energy systems. LMDI decomposition method based on energy allocation analysis for CO2 emissions. GDP per capital, population and end-use fuel-mix changes increased CO2 emissions. Energy intensity and electricity efficiency changes decrease CO2 emissions.